Redesigning payments for ecosystem services to increase cost-effectiveness (2024)
Payments for Ecosystem Services (PES) are a widely used approach to incentivize conservation efforts such as avoided deforestation. Although PES effectiveness has received significant scholarly attention, how PES design modifications can improve program outcomes is less explored. We present findings from a randomized trial in Mexico that tested whether a PES contract that requires enrollees to enroll all of their forest is more effective than the traditional PES contract that allows them to choose which forest parcels to enroll. The modification’s aim is to prevent landowners from enrolling only parcels they planned to conserve anyway while leaving aside other parcels to deforest. We find that the full-enrollment treatment significantly reduces deforestation compared to the traditional contract (41% less deforestation